The Key to a Quality Life - Afiani, Nur (Research of Service Administration Health and Sains Healthys, 2024)
This research aims to identify and analyze factors that contribute to a good quality of life. Physical health, mental health, social health, and a healthy lifestyle are considered the main components that influence quality of life. This research uses mixed methods which combine qualitative and quantitative approaches. Quantitative data was collected through a questionnaire survey from 200 respondents covering various aspects of health and lifestyle. Qualitative data was obtained through in-depth interviews with 20 participants as well as direct observation to gain a deeper understanding of individual experiences and views on quality of life. Quantitative analysis shows that there is a significant positive correlation between physical activity, healthy eating patterns, social support and mental health with the level of quality of life. Qualitative analysis identified four main themes: the importance of maintaining physical health through exercise and a healthy diet; mental health through relaxation techniques and emotional support; social health through meaningful interactions and relationships; and a healthy lifestyle that includes daily habits that support overall well-being. This research concludes that a good quality of life can be achieved through a balance between physical, mental and social health, as well as implementing a healthy lifestyle. Support from government and society is also important in creating an environment that supports holistic health. These findings can form the basis for public health programs and policies aimed at improving people's quality of life.